Impact of the Covid-19 pandemic on air transport - Filipiak Dariusz; Matyjaszkiewicz Magdalena A.; Zalewski Piotr; Postek Joanna (2023)
The purpose of this article is to present the impact of the Covid-19 pandemic on the operation of airlines and the aviation sector as a whole. The pandemic forced airlines to make many changes in their operations and greatly affected the entire aviation sector. The operation of the aviation sector during the pandemic period was affected by the administrative closure of flights for months, as well as the regulation banning flights to selected countries.